Biomarkers are associated with clinical and endoscopic outcomes with vedolizumab treatment in Crohn's disease. (November 2020) - Holmer, Ariela K.; Battat, Robert; Dulai, Parambir S.; Vande Casteele, Niels; Nguyen, Nghia; Jain, Anjali; Miralles, Ara; Neill, Jennifer; Le, Helen; Singh, Siddharth; Rivera-Nieves, Jesus; Sandborn, William J.; et al.
Background: Vedolizumab, an α4β7 integrin antagonist, is an effective therapy for Crohn's disease (CD). Biomarkers are needed to guide therapy and predict outcomes. This study evaluated biomarker concentrations and outcomes in patients with CD undergoing vedolizumab treatment. Methods: Sera at weeks 0, 2, 6, 14, and ⩾26 were collected from vedolizumab-treated, refractory CD patients. Concentrations of soluble (s)-Vascular Cell Adhesion Molecule (VCAM)-1, s-Intercellular Cell Adhesion Molecule (ICAM)-1, s-Mucosal Addressin Cell Adhesion Molecule (MAdCAM)-1, and s-α4β7 integrin were evaluated for associations with achieving endoscopic remission. Results: A total of 22 patients with CD were included. In all patients, s-MAdCAM-1 decreased significantly and s-α4β7 increased compared with baseline. s-VCAM-1 and s-ICAM-1 changed differentially in patients who achieved remission. At week 6, median s-VCAM-1 (859.6 ng/ml versus 460.3 ng/ml, p = 0.03) and s-ICAM-1 (545.7 ng/ml versus 286.2 ng/ml, p = 0.03) concentrations were higher in patients who achieved endoscopic remission compared with those who did not, and similar differences were observed for s-ICAM-1 concentrations in patients who achieved clinical remission, compared with those who did not (669.1 ng/ml versus 291.0 ng/ml, p = 0.04). Week 14 s-α4β7 concentrations were lower in patients who achieved endoscopic remission, compared with those who did not (7.5 ng/ml versus 17.6 ng/ml, p = 0.020). Conclusion: In all vedolizumab-treated CD patients, s-MAdCAM-1 decreased significantly and s-α4β7 increased. However, higher concentrations of s-ICAM-1 and s-VCAM-1 at week 6 and lower concentrations of s-α4β7 at week 14 differentiated patients who achieved endoscopic remission. These findings may help identify early predictors of response to vedolizumab treatment in patients with CD. Further validation in less refractory CD patients is needed.